Haemophilus pittmaniae and Leptotrichia spp. Constitute a Multi-Marker Signature in a Cohort of Human Papillomavirus-Positive Head and Neck Cancer Patients - Mougeot, Jean-Luc C.; Beckman, Micaela F.; Langdon, Holden C.; Lalla, Rajesh V.; Brennan, Michael T.; Bahrani Mougeot, Farah K. (Frontiers in Microbiology, 2022)
Objectives Human papillomavirus (HPV) is a known etiological factor of oropharyngeal head and neck cancer (HNC). HPV positivity and periodontal disease have been associated with higher HNC risk, suggesting a role for oral bacterial species. Our objective was to determine oral microbiome profiles in HNC patients (HPV-positive and HPV-negative), and healthy controls (HC). Methods Saliva samples and swabs of buccal mucosa, supragingival plaque and tongue were collected from HNC patients (N=23 pts, n=92 samples) before cancer therapy. Next generation sequencing (16S-rRNA gene V3-V4 region) was used to determine bacterial taxa relative abundance (RA). beta-diversities of HNC-HPV+ (N=16 pts, n=64 samples) and HNC-HPV- (N=7pts, n=28 samples) groups were compared using PERMANOVA (pMonte-Carlo<0.05). LEfSe discriminant analysis was performed to identify differentiating taxa (Log-LDA>2.0). RA differences were analyzed by Mann-Whitney U-test (alpha=0.05). CombiROC program was used to determine multi-marker bacterial signatures. The microbial interaction network database (MIND) and LitSuggest online tools were used for complementary analyses. Results HNC vs. HC and HNC-HPV+ vs. HNC-HPV- beta-diversities differed significantly (pMonte-Carlo<0.05). Streptococcus was the most abundant genus for HNC and HC groups. Rothia mucilaginosa and Haemophilus parainfluenzae were the most abundant species in HNC and HC patients, respectively, regardless of antibiotics treatment. LEfSe analysis identified 43 and 44 distinctive species for HNC-HPV+ and HNC-HPV- groups, respectively. In HNC-HPV+ group, 26 periodontal disease-associated species identified by LefSe had a higher average RA compared to HNC-HPV- group. The significant species included Alloprevotella tannerae, Fusobacterium periodonticum, Haemophilus pittmaniae, Lachnoanaerobaulum orale, and Leptotrichia spp. (Mann-Whitney U-test, p<0.05). Of 43 LEfSe-identified species in HPV+ group, 31 had a higher RA compared to HPV- group (Mann-Whitney U-test, p<0.05). MIND analysis confirmed interactions between Haemophilus and Leptotrichia spp., representing a multi-marker signature per CombiROC analysis (AUC>0.9). LitSuggest correctly classified 15 articles relevant to oral microbiome and HPV status. Conclusion Oral microbiome profiles of HNC-HPV+ and HNC-HPV- patients differed significantly regarding periodontal-associated species. Our results suggest that oral bacterial species (e.g., Leptotrichia spp.), possessing unique niches and invasive properties, coexist with HPV within HPV-induced oral lesions in HNC patients. Further investigation into host-microbe interactions in HPV-positive HNC patients may shed light into cancer development.